Bilayered Oxide‐Based Cognitive Memristor with Brain‐Inspired Learning Activities. (25th June 2019) - Xiong, Wen; Zhu, Li Qiang; Ye, Cong; Yu, Fei; Ren, Zheng Yu; Ge, Zi Yi
Abstract: Recently, neuromorphic devices have attracted great attention due to their potential to overcome the von Neumann bottleneck. Due to their nonlinear electrical characteristics and nonvolatile resistance, memristors have been proposed for use in neuromorphic device applications. Bilayered HfO2 /TiO x ‐based cognitive memristors are proposed. They demonstrate conductance‐modulation capabilities at low operation voltage. Moreover, they can be used to mimic the learning behaviors of biological synapses. The multistore memory model of the brain is exhibited. Furthermore, four types of spike‐timing‐dependent plasticity leaning rules are mimicked by modulating the pre‐ and postsynaptic spikes. In addition, pattern learning and memory behaviors are mimicked. These results indicate that the Pt/HfO2 /TiO x /TiN cognitive memristor has potential for applications in neuromorphic platforms. Abstract : Bilayered HfO2 /TiO x ‐based cognitive memristors are fabricated. They demonstrate conductance modulation capabilities at low operation voltage. Synaptic learning behaviors are mimicked, including the multistore memory model of brain, a number of spiking‐timing‐dependent plasticity learning rules, and pattern learning and memory behaviors. These cognitive memristors have potential applications in neuromorphic platforms.